2008
DOI: 10.1016/j.transci.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of immature platelets for decision making regarding platelet transfusion indications for pediatric patients

Abstract: Immature or reticulated platelets are known as a clinical marker of thrombopoiesis. Recently, an automatic method was established to detect reticulated platelets as immature platelet fraction (IPF) by means of hematology analyzer XE-2100. We assessed the effects of IPF detection after chemotherapy for various pediatric malignant disorders of 16 patients. Our results indicate that IPF should be considered a useful marker of imminent platelet recovery so that unnecessary platelet transfusion can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 8 publications
6
34
0
1
Order By: Relevance
“…In this study, the IPF percentage of non-thrombocytopenic neonates was negatively correlated with gestational age, which was consistent with a previous report [18]. A significant inverse correlation between platelet count and IPF percentage was reported in patients with immune thrombocytopenic purpura (ITP) [11,12,19]. The IPF percentage may reflect the severity of platelet destruction and/or increased platelet production.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the IPF percentage of non-thrombocytopenic neonates was negatively correlated with gestational age, which was consistent with a previous report [18]. A significant inverse correlation between platelet count and IPF percentage was reported in patients with immune thrombocytopenic purpura (ITP) [11,12,19]. The IPF percentage may reflect the severity of platelet destruction and/or increased platelet production.…”
Section: Discussionsupporting
confidence: 92%
“…Following peripheral blood stem cell transplant in adults, the IPF% value rises 1-2 days prior to the increment in platelet count [23,25]. Saigo et al [30] observed platelet recovery within 3-7 days after the day of peak IPF% in pediatric patients with various malignant disorders after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This creates the opportunity to defer platelet transfusions that would be given when transfusion decisions are based on platelet counts only. Until present, limited clinical evidence supporting this concept has been reported and there is an evident need for randomized, controlled clinical studies in this field [82,97,98]. A highly interesting observation that also needs to be confirmed is that prophylactic transfusions with high IPF platelet concentrates seem to be more effective than low IPF platelets [99].…”
Section: Clinical Utility Of Reticulated/ Immature Plateletsmentioning
confidence: 99%